Agricultura científica globalizada e fronteira agrícola moderna no Brasil - Samuel Frederico (Confins)
This article analyzes the dissemination of global scientific agriculture in the Brazilian modern agricultural frontier. In the 1990s, there is a new agricultural production paradigm characterized by: the new technologies of information, for less State intervention, the regulation of companies, the internationalization of trade, the regional productive specialization and the financialization of agricultural commodities. The global scientific agriculture increases the production efficiency, but creates greater vulnerability to social, economic and territorial.